Hip Desarthrodesis - Report of Three Cases - Moura, DL (2020)
Hip desarthrodesis, which is the conversion of an arthrodesis or of a surgical bone fusion into a hip replacement arthroplasty, is a difficult and challenging operation because of the need of a joint reconstruction in cases with bone fusion and an often long-term immobilization between the femur and the acetabulum, with important anatomic changes, retractions of adjacent soft tissues, and an associated limb shortening. Hip arthrodesis is an operation performed less and less; consequently, its desarthrodesis is even rarer. The present report details three rare cases of patients with long-term hip arthrodesis who were submitted to hip replacement conversion arthroplasty; it describes the applied surgical techniques and their clinical and functional outcomes.